I. Papers relating to President John F. Kennedy - Farrell, Brian, 1929- (1959)
These papers relate primarily to President John F. Kennedy's visit to Ireland in 1963, and consist of original documentation relating to the visit, notably schedules of events, press releases and documentation relating to the RTÉ coverage of the visit. Also included are newspaper cuttings, magazines and books relating to Kennedy, manuscript and typscripts drafts of radio programmes, written by Farrell on Kennedy's death and subsequently broadcast on Radio Éireann in November 1963 and some documentation relating to an event organised by the John Fitzgerald Kennedy Association of Ireland in 1965.
These papers were compiled by academic and broadcaster Brian Farrell. Having worked for Radio Éireann in the 1950's, Farrell went onto join the staff of Raidió Teilifís Éireann in the early 1960s and was among the RTÉ personnel that covered President Kennedy's visit to Ireland.
Keywords: Kennedy, John F. -- 1917-1963; United States -- Politics and government -- 20th century